Hot cold tumbler - Chong, Chee Keong (2017)
Thermoelectric effect has created a lot of impacts in human life. Since 1894, we developed so many ways of making use of thermoelectric for preserving food, cooling water, and heating. Nowadays, people are looking for products which are cheap, efficient and long lasting. Our research focused on inculcating all these characteristics and enables users to carry a multifunctional bottle anywhere and everywhere. Our tumbler enables users to choose to prepare hot or cold water with just a click of a button and it only takes around 30 minutes. When the water reached the desired temperature, user will be able to consume the water directly from our bottle or even make delicious drinks. The bottle is portable, reusable and affordable. The goal is to produce a controller circuit that can control the heating and cooling process of the Peltier chip and find a proper power supply for the system.